Проблемы современного обучения и рекомендации по подготовке инженеров-преподавателей в Украине - Лизан, Игорь Ярославович; Шевченко, Валентина Владимировна; Михальченко, А. Г. (Издательский центр Донского государственного технического университета, 2011)
Промышленность страны требует подготовки специалистов нового типа, у которых должно быть сформировано четкое понимание требований современного производства. Особенное внимание следует уделять профессиональной компетенции будущих инженеров-преподавателей, определению роли практической направленности их подготовки, решению вопросов контроля их знаний, умению видеть технические проблемы, разрешать их с учетом современных возможностей науки и техники. Сделаны предложения по изменению рабочих программ и особенностям подготовки инженеров-преподавателей.

Industry of country requires preparations of specialists of new type, at which it must be formed the clear understanding of requirements of modern production. The special attention is necessary to spare to professional jurisdiction of future engineers-teachers, to determination of role of practical orientation of their preparation, decision of questions of control of their knowledge, ability to see technical problems, settle them taking into account modern possibilities of science and technique. Suggestions are done on the change of executable codes and features of preparation of engineers-teachers.
Problems of modern education and recommendations for the training of engineers-teachers in Ukraine
Keywords: инженерная педагогика; профессиональная компетентность; практическая подготовка; инновационная проектная деятельность; структура подготовки; энергосбережение; engineering pedagogies; professional competence; practical preparation; innovative project activity; structure of preparation; conservation of energy